Online Human Rights? Towards a Cosmopolitan Framework for Internet Policymaking in the Digital Era - Muñoz-González, Rodrigo (2018)
This article discusses an important challenge for Internet governance: the difficulties entailed in articulating the multiplicity of scenarios and contexts that shape it. A “multistakeholder” approach has been posited often as the most suitable path to build Internet governance. However, materializing this approach is difficult because of the possible actors and situations found on the Web. Instead, and building on the notion of cosmopolitanism (Boczkowski & Siles, 2014), this article proposes an alternative framework for studying Internet policymaking. It applies this framework to the Digital Privacy and Security Statement advanced by the Global Commission on Internet Governance in order to show how it can help further our understanding of Human Rights in the digital era. It argues that cosmopolitanism can offer a method that helps to transform a complex network of interactions into a map characterized by different objectives and relations in order to generate more dialectic Internet policies.